The Influence of Hard Skills and Career Development on Employee Performance Achievement at the Makassar City Transportation Service - Risfayanti Rustam; Moh Aris Pasigai; Zalkha Soraya (CV. AFDIFAL MAJU BERKAH, 2024)
To determine the influence of the Hard Skills and Career Development Towards Employee Performance Achievement At the Makassar City Transportation Department. To analyze this research, the method used is quantitative descriptive with the number of samples taken as many as 89 respondents from the total population as many as 787 people at the Makassar City Transportation Service Using the Slovin formula. The data analysis technique using multiple linear regression and data collection techniques are carried out through observation, questionnaires and documentation. The research results show that the influence of Hard Skills and Career Development on the performance of Makassar City Transportation Service employees positive and significant effect on the performance of Makassar City Transportation Service employees.